LIVE ANTIVARIOLIC VACCINES - R. A. Maksyutov (Проблемы особо опасных инфекций, 2017)
Smallpox eradication due to global vaccination is still one of the paramount triumphs of medical science. Given the termination of the subsequent immunization, nowadays humanity virtually possesses no antivariolic immunity and is unprotected against the pathogenic for humans orthopoxviruses. Utilization of the first-generation traditional live vaccines, obtained with the help of the virus replication on calf skin, or the second-generation preparation, produced in mammalian cell cultures or grown on bird embryos, for mass vaccination is currently unacceptable in view of considerable increase in immune deficiency states among the human population within the recent decades. Attenuated non-replicating antivariolic vaccines of the third generation, obtained in the process of multiple vaccinia virus (VV) passage on cell cultures of heterologous host, induce weaker antivariolic response as compared to traditional vaccine. The most prospective approach is to produce the vaccines of the fourth generation, applying targeted VV genes’ mutation, which control protective reactions of an organism against viral infection, as well as host range genes and the genes involved in nucleic acid metabolism, while skipping the genes responsible for virus replication. Novel attenuated and highly immunogenic strain, VV LIVPΔ6, having mutations in 6 virulence genes, is presently in the phase of pre-clinical trial and later on it may turn an effective and safe vaccine of the fourth generation against smallpox and other orthopoxvirus infections in humans.